A Synthesis of Quantitative Research on Reading Programs for Secondary Students. Issue 2 (23rd September 2018) - Baye, Ariane; Inns, Amanda; Lake, Cynthia; Slavin, Robert E.
Abstract: Recent initiatives in the United States and United Kingdom have added greatly to the amount and quality of research on the effectiveness of secondary reading programs, especially programs for struggling readers. In this review of the experimental research on secondary reading programs, the authors focused on 69 studies that used random assignment ( n = 62) or high‐quality quasi‐experiments ( n = 7) to evaluate outcomes of 51 programs on widely accepted measures of reading. Categories of programs using one‐to‐one and small‐group tutoring, cooperative learning, whole‐school approaches including organizational reforms such as teacher teams, and writing‐focused approaches showed positive outcomes. Individual approaches in a few other categories also showed positive impacts. Categories in which these individual programs appear include programs emphasizing social studies/science, structured strategies, and personalized and group/personalization rotation approaches for struggling readers. Programs that provide a daily extra period of reading and those utilizing technology were no more effective, on average, than programs that did not provide these resources. The findings suggest that secondary readers benefit more from socially and cognitively engaging instruction than from additional reading periods or technology.